Analisis Produksi Maggot yang Dibudidayakan Dalam Rangka Pemanfaatan Food Waste di Wilayah Depok Jawa Barat - Nur Audi Larasati; Fariz Am Kurniawan; Annisa Hakim; Pria Sembada; Gilang Ayuningtyas; Sari Putri Dewi (Politeknik Pertanian Bogor, 2025)
Bioconversion using Black Soldier Fly (BSF) maggots has proven effective in degrading organic waste and producing nutritious plant fertilizers. The different growth media used in bioconversion can affect the quality of the resulting maggots. This study aims to analyze the impact of different growth media on maggot productivity. The study employed a Completely Randomized Design (CRD) with four different growth media treatments: P0=100% Kitchen Organic Waste (KOW); P1=100% cow manure; P2=50% KOW and 50% cow feces; P3= 50% KOW and 50% dairy product. The results indicated that the different growth media significantly affected the productivity of the resulting maggots. Treatment P3 produced the highest fresh maggot biomass at 3800 g from 2 g BSF eggs. The processing of BSF maggots involved drying the maggots using the roasting method, with roasting for 10-15 minutes. As a result, the dried maggots can be stored for longer periods and made into maggot meal. The growth medium of KOW and dairy product mixture produced the most optimal maggots compared to other treatments. Treatment P1 has potential as an alternative maggot growth medium that accelerates composting and effectively produces maggot compost. It is recommended that cow feces be mixed with more nutritious media such as KOW and milk waste. Additional treatment levels can be applied in further research to determine the best growth media for BSF maggot cultivation.